STAT5a promotes the transcription of mature mmu-miR-135a in 3T3-L1 cells by binding to both miR-135a-1 and miR-135a-2 promoter elements. (August 2016) - Wei, Xiajie; Cheng, Xiaoyan; Peng, Yongdong; Zheng, Rong; Chai, Jin; Jiang, Siwen
Highlights: Intragenic miR-135a-1 and miR-135a-2 are independently transcribed. Both miR-135a-1 and miR-135a-2 are regulated by STAT5a. STAT5a up-regulates miR-135a expression. STAT5a and APC have negative feedback during 3T3-L1 adipogenic differentiation. Abstract: Despite extensive research on the role of miR-135a in biological processes, very little attention has been paid to the regulation of its transcription. We have previously reported that miR-135a suppresses 3T3-L1 preadipocyte differentiation and adipogenesis by directly targeting the adenomatous polyposis coli ( APC ) gene and activating the canonical Wnt/β-catenin signaling pathway, but the regulatory elements that regulate the expression of the two isoforms of miR-135a (miR-135a-1 and miR-135a-2) remain poorly understood. Here, by using deletion analysis, we predicted two binding sites (−874/−856 and −2020/−2002) for the transcription factor Signal Transducers and Activators of Transcription 5a (STAT5a) within the core promoters of miR-135a-1 and miR-135a-2 (−1128/−556 and −2264/−1773), and the subsequent site-directed mutagenesis indicated that the two STAT5a binding sites regulated the activity of the miR-135a-1 and miR-135a-2 promoters. The binding of STAT5a to the miR-135a-1/2 core promoters in vitro and in cell culture was identified by electrophoretic mobility shift assays (EMSA) and chromatin immunoprecipitation (ChIP) assays. Overexpression and RNAi knockdown of STAT5a showed that the transcription factor regulated the endogenous miR-135a expression. Additionally, The expression time frame of STAT5a and APC indicated a potential negative feedback between them. In sum, the overall results from this study indicate that STAT5a regulates miR-135a transcription by binding to both miR-135a-1 and miR135a-2 promoter elements and the findings provide novel insights into the molecular regulatory mechanisms of miR-135a during adipogenesis.